Health Education : Audio Visual Media for Improving Mother’s Knowledge, Attitude, and Psychomotor of Breastfeeding Techniques : Pendidikan Kesehatan Media Audio Visual Untuk Meningkatkan Pengetahuan, Sikap dan Psikomotor Ibu Tentang Tehnik Menyusui - Mukhoirotin; Masruroh, Siti (Universitas Muhammadiyah Sidoarjo, 2022)
Lack of mother's knowledge about the correct management of lactation is the cause of mothers cannot breastfeed their babies with the correct technique which results in the baby not being able to suck effectively. If this condition is not treated, it will affect the growth of the baby, the growth and development of the baby is hampered. Efforts that can be made to deal with these problems are by providing health education with audiovisual media. The aim is to determine the effect of health education on mother's knowledge, attitudes and psychomotor about breastfeeding techniques. This study uses a Quasy-Exsperiment design, Pretest-Postest Control Group Design. The population in this study were all postpartum mothers at Paviliun Melati RSUD Jombang. The research subjects were 30 treatment respondents and 30 control respondents, using purposive sampling technique. Data were analyzed using Wilcoxon and Mann-Whitney with a significance level of 0.05. The results of the analysis test showed that there was an effect of health education on mother's knowledge, attitudes and psychomotor about breastfeeding techniques with a significance value of p<0.05, and there were differences in the effect of health education on mother's knowledge, attitudes and psychomotor about correct breastfeeding techniques in the group. treatment and control groups with a significance value of p<0.05. Health education uses effective audiovisual media to increase mother's knowledge, attitudes and psychomotor about breastfeeding techniques and can be used as alternative media in an effort to provide health information.